1977
DOI: 10.1136/bjo.61.9.573
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the outer retinal layers following blunt mechanical non-perforating trauma to the globe: an experimental study.

Abstract: SUMMARY Structural changes in the external retinal layers of pigs' eyes that had previously been subjected to blunt non-perforating mechanical injuries have been described. Within minutes of trauma fragmentation of the photoreceptor outer segments and damage to the retinal pigment epithelium was recorded in areas of retina adjacent to the missile impact site on the sclera. One week after injury the disrupted photoreceptor outer segments disappeared, and the inner segments came to lie adjacent to the retinal pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
10

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 9 publications
2
22
0
10
Order By: Relevance
“…In five eyes ruptures involving the fovea appeared to be directly responsible for a reduction in vision. However, in a further 10 eyes with macular damage the Delayed complications may occur after concussional eye injuries,"' leading to further (or late) visual loss, and 8/30 of our series developed changes which could have led to a further deterioration in visual function (one patient with glaucoma, two with retinal detachments, five developing subretinal neovascular membranes).…”
Section: Resultsmentioning
confidence: 99%
“…In five eyes ruptures involving the fovea appeared to be directly responsible for a reduction in vision. However, in a further 10 eyes with macular damage the Delayed complications may occur after concussional eye injuries,"' leading to further (or late) visual loss, and 8/30 of our series developed changes which could have led to a further deterioration in visual function (one patient with glaucoma, two with retinal detachments, five developing subretinal neovascular membranes).…”
Section: Resultsmentioning
confidence: 99%
“…Na contusão retiniana, o esbranquiçamento é mais intenso, há microhemorragias e baixa visual acentuada (6) . Estudos histopatológicos em animais e humanos revelaram que commotio retinae é uma doença predominantemente da retina externa, com desorganização dos segmentos externos dos fotorreceptores e resposta fagocítica do EPR (2)(3)7) . As imagens do OCT permitem estudo anatômico não invasivo in vivo da retina, e em relatos prévios de concussão retiniana são correlatos com achados histológicos: hiper-refletividade e espaços opticamente vazios na região do segmento externo dos fotorreceptores.…”
Section: Discussionunclassified
“…A hiper-refletividade na retina externa e no EPR provavelmente corresponde à grave desorganização do segmento externo dos fotorreceptores e dos corpos celulares, assim como à ativação fagocítica do EPR. O aumento da refletividade interna da retina no OCT não havia ainda sido relatada, talvez porque todos os casos já relatados readquiriram visão normal em sua evolução, correspondendo a casos com lesões onde prepondera o componente de concussão e não de contusão retiniana (4)(5)7) . Seis meses após o trauma observou-se redução da espessura retiniana foveal com região hiper-refletiva intrarretiniana permanente, assim como irregularidades do EPR, compatíveis com as alterações pigmentares vistas à fundoscopia, que sugerem desorganização e cicatrização irreversíveis de EPR e retina após a contusão.…”
Section: Discussionunclassified
“…In the posterior segment, blunt ocular trauma may cause damage to the retina (commotio retinae), retinal epithelium (retinal pigment epithelium edema), choroid (choroid rupture) and optic nerve (optic nerve avulsion) alone or in combination. Traumatic retinal holes, retinal detachment or dialysis, vitreous hemorrhage and arterial occlusion may also occur after blunt ocular trauma [16][17][18][19]. In one study loss of contrast sensitivity following blunt ocular trauma was found.…”
Section: Introductionmentioning
confidence: 99%
“…The more severe the structural abnormalities of the eye were, the more marked was the difference in contrast sensitivity between normal and injured eyes [20]. The major site of injury in commotio retinae seems to be at the level of photoreceptor outer segment-retinal pigment epithelium junction [18,19].…”
Section: Introductionmentioning
confidence: 99%